TEACHING MEDICINE VOCABULARY THROUGH TPR METHOD FOR ESP LEARNERS - Nazarova Nilufar Baxtiyorovna; Valiyeva Zuhra Baxriddin qizi; Akbarova Sarvinoz Ahmad qizi (Ustozlar uchun, 2025)
This study explores the effectiveness of the Total Physical Response (TPR) method in teaching medical vocabulary to English for Specific Purposes (ESP) learners. Forty intermediate-level medical students and nurses in Uzbekistan were divided into an experimental group taught using TPR and a control group taught with traditional methods (e.g., flashcards, translation). Over eight weeks, the TPR group associated vocabulary with physical actions, while the control group used conventional techniques. Pre-tests, post-tests, and retention tests assessed vocabulary acquisition, and surveys evaluated learner engagement and confidence. Results showed the TPR group significantly outperformed the control group in post-test and retention test scores. TPR learners also reported higher engagement and confidence . Findings suggest TPR enhances vocabulary retention and engagement, making it a valuable approach for ESP medical English instruction. Further research is needed to address its applicability to abstract terms and broader contexts.